2011
DOI: 10.1097/iae.0b013e3181eac7a6
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Tumor Necrosis Factor Inhibitors in the Treatment of Refractory Diabetic Macular Edema

Abstract: Both intravitreal adalimumab and infliximab do not appear to benefit eyes with refractory diabetic macular edema. Intravitreal injections of infliximab may elicit a severe intraocular inflammatory reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 28 publications
2
52
0
2
Order By: Relevance
“…Inflammatory reactions were also observed by Wu and colleagues in 8 patients with diabetic macular edema (20% of total patients) who underwent intravitreal injection of infliximab (2 mg) (24) similar to 4 cases reported by Giganti and colleagues who injected infliximab (0.5 mg) in 2 patients with macular edema and 2 patients with neovascular ARMD where 100% of the patients showed uveitis (25) . Both infliximab and bevacizumab are monoclonal humanized antibodies.…”
Section: Discussionsupporting
confidence: 56%
“…Inflammatory reactions were also observed by Wu and colleagues in 8 patients with diabetic macular edema (20% of total patients) who underwent intravitreal injection of infliximab (2 mg) (24) similar to 4 cases reported by Giganti and colleagues who injected infliximab (0.5 mg) in 2 patients with macular edema and 2 patients with neovascular ARMD where 100% of the patients showed uveitis (25) . Both infliximab and bevacizumab are monoclonal humanized antibodies.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, the adhesion of monocytes, neutrophils and other leukocytes in experimental DR is likely to be enhanced by the release of chemokines from retinal tissue, the expression of adhesion molecules on the retinal vasculature, and the expression of integrins by circulating leukocytes. [156,157]. In fact, these studies found adverse effects, including vitritis and uveitis, in some eyes receiving Inflixamab.…”
Section: Additional Cytokines In Drmentioning
confidence: 96%
“…21 Those data suggested that both intravitreal adalimumab and intravitreal infliximab had no effect on refractory diabetic macular edema. Moreover, intravitreal injections of infliximab may lead to serious intraocular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intravitreal injections of infliximab may lead to serious intraocular inflammation. 21 On the other hand, IVA did not lead to retinal damage in animal models at a dose of 0.5 mg in one study 22 and up to 5 mg in another study. 23 No information is available on the stability and efficacy of reconstituted or aliquoted adalimumab for multiple use to date.…”
Section: Discussionmentioning
confidence: 99%